Abundance of Ixodes ricinus and prevalence of Borrelia burgdorferi s.l. in the nature reserve Siebengebirge, Germany, in comparison to three former studies from 1978 onwards - Schwarz, Alexandra; Hönig, Václav; Vavrušková, Zuzana; Grubhoffer, Libor; Balczun, Carsten; Albring, Antje; Schaub, Günter A (Parasites & vectors, 2012)
BACKGROUND: During the last decades, population densities of Ixodes ricinus and prevalences of Borrelia burgdorferi s.l. have increased in different regions in Europe. In the present study, we determined tick abundance and the prevalence of different Borrelia genospecies in ticks from three sites in the Siebengebirge, Germany, which were already examined in the years 1987, 1989, 2001 and 2003. Data from all investigations were compared. METHODS: In 2007 and 2008, host-seeking I. ricinus were collected by monthly blanket dragging at three distinct vegetation sites in the Siebengebirge, a nature reserve and a well visited local recreation area near Bonn, Germany. In both years, 702 ticks were tested for B. burgdorferi s.l. DNA by nested PCR, and 249 tick samples positive for Borrelia were further genotyped by reverse line blotting. RESULTS: A total of 1046 and 1591 I. ricinus were collected in 2007 and 2008, respectively. In comparison to previous studies at these sites, the densities at all sites increased from 1987/89 and/or from 2003 until 2008. Tick densities and Borrelia prevalences in 2007 and 2008, respectively, were not correlated for all sites and both years. Overall, Borrelia prevalence of all ticks decreased significantly from 2007 (19.5%) to 2008 (16.5%), thus reaching the same level as in 2001 two times higher than in 1987/89 (7.6%). Since 2001, single infections with a Borrelia genospecies predominated in all collections, but the number of multiple infections increased, and in 2007, for the first time, triple Borrelia infections occurred. Prevalences of Borrelia genospecies differed considerably between the three sites, but B. garinii or B. afzelii were always the most dominant genospecies. B. lusitaniae was detected for the first time in the Siebengebirge, also in co-infections with B. garinii or B. valaisiana. CONCLUSIONS: Over the last two centuries tick densities have changed in the Siebengebirge at sites that remained unchanged by human activity since they belong to a nature reserve. Abiotic and biotic conditions most likely favored the host-seeking activity of I. ricinus and the increase of multiple Borrelia infections in ticks. These changes have led to a potential higher risk of humans and animals to be infected with Lyme borreliosis.
Keywords: časové faktory; Prevalence; Ixodes; Time Factors; Germany; Borrelia burgdorferi komplex; Polymerase Chain Reaction; polymerázová řetězová reakce; prevalence; DNA, Bacterial; DNA bakterií; klíště; Animals; Borrelia burgdorferi Group; zvířata; Population Density; hustota populace; Německo